Perencanaan Struktur Gedung Kuliah 5 Lantai Dengan Sistem Daktail Penuh Di Wilayah Gempa 3 - Wahyono, Riksa Daru; , Ir. Abdul Rochman, M.T; , Muhammad Ujianto, ST, MT (2015)
Planning srtuctural storey building at Indonesia, planning that structural has earth quake resistance which match to Standart National Indonesia. The title of the final task is "Perencanaan Gedung Kuliah 5 lantai dengan Sistem Daktail Penuh Di Wilayah Gempa 3" using some direction: 1. SNI 03-2847-2002 2. SNI 03-1726-2002 3. SNI 03-1729-2002 And using some software that is Microsoft Excel, Microsoft Word, Autocad 2007, Sap 2000 v11. The Planning this storey building in Surakarta area which 3rd earth Quake Area with the hard soil structural. Level of performance building is full ductile with the ductility factor (μ) = 5,3 and the earthquake reduction factor (R) = 8,5. The steel quality is Bj 41. Roof Structure using IWF steel (244.175.11.7) in main structure and IWF structure (125.80.9.8) in second structure. Distance between other foundation of roof structure is 20m. The Portal Structure 5th floor use reinforced concrete. Fondation using rectangular piles with dimension 30x30 cm 2 , and to drive piles is 6m underground.